Anti-aging and anti-corrosion coating and preparation method thereof

By using modified acrylic resins and modified titanium dioxide nanosheets, the problems of aging accelerated aging and lack of corrosion resistance, flame retardant and antibacterial properties in long-term use of traditional coatings are solved, and the performance and service life of anti-aging and corrosion-resistant coatings are improved and the service life of anti-aging and corrosion-resistant coatings are extended.

CN119592220AInactive Publication Date: 2025-03-11HUBEI HONGCHENG COATING TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411569087.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional coatings are susceptible to environmental factors in long-term use, resulting in accelerated aging, lack of corrosion resistance, flame retardant and antibacterial properties, and cannot effectively protect the substrate in highly corrosive application scenarios.

Method used

Modified acrylic resin and modified titanium dioxide nanosheets are used as main components to form an anti-aging and corrosion-resistant coating with excellent anti-corrosion, anti-aging, flame retardant and anti-bacterial properties through specific chemical reactions and treatment methods.

Benefits of technology

It has achieved significant improvements in the anti-corrosion, anti-aging, flame retardant and anti-bacterial properties of the paint, extended the service life of the coating, and provided higher guarantees in terms of fire safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119987890000141
    Figure BDA0005119987890000141
Patent Text Reader

Abstract

The invention discloses an anti-aging and anti-corrosion coating and a preparation method thereof, and relates to the technical field of coatings. When the anti-aging and anti-corrosion coating is prepared, firstly, tetramethyl tetravinyl cyclotetrasiloxane, n-butyllithium and dimethyl-3-chloropropyl chlorosilane react to obtain modified polysiloxane, then 4-vinylpyridine, methyl methacrylate and n-butyl acrylate are copolymerized and then react with the modified polysiloxane, and then bis (4-chlorphenyl) phosphine is grafted to obtain the anti-aging and anti-corrosion coating. Finally, reacting with p-aminodiphenylamine to obtain modified acrylic resin; secondly, enabling the titanium dioxide nanosheet pretreated by 3-aminopropyltrimethoxysilane to react with ester phthalocyanine, and then hydrolyzing to obtain a modified titanium dioxide nanosheet; finally, mixing the modified acrylic resin, the modified titanium dioxide nanosheet, a solvent, a dispersing agent and a defoaming agent to obtain the anti-aging and anti-corrosion coating. The anti-aging and anti-corrosion coating prepared by the invention has excellent anti-aging, anti-corrosion, flame-retardant and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to an anti-aging and anti-corrosion coating and a preparation method thereof. Background Art

[0002] In the current industrial and architectural fields, coatings are the first line of defense against environmental erosion, and their importance is self-evident. Traditional coatings face many challenges in long-term use. Their significant disadvantages include being susceptible to environmental factors such as ultraviolet radiation, high temperature and humidity changes, which lead to accelerated aging and reduce the protective performance and service life of the coating.

[0003] At the same time, the ability to resist corrosive environments is insufficient, especially in highly corrosive application scenarios such as chemical and marine applications, the coating is easily damaged and falls off, and cannot effectively protect the substrate; in addition, traditional coatings often lack antibacterial properties; more importantly, most traditional coatings lack the necessary flame retardant properties when encountering a fire source, and cannot effectively prevent the spread of the fire, bringing hidden dangers to fire safety. The anti-aging and anti-corrosion coating prepared by the present invention has excellent anti-corrosion, anti-aging, flame retardant and antibacterial properties. Summary of the invention

[0004] The purpose of the present invention is to provide an anti-aging and anti-corrosion coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an anti-aging and anti-corrosion coating, which is obtained by mixing modified acrylic resin, modified titanium dioxide nanosheets, solvent, dispersant and defoamer.

[0007] As an optimization, the modified acrylic resin is a pyridyl acrylic resin obtained by copolymerizing 4-vinylpyridine, methyl methacrylate, and n-butyl acrylate; the pyridyl acrylic resin is reacted with a modified polysiloxane, then grafted with bis(4-chlorophenyl)phosphine, and finally reacted with p-aminodiphenylamine; the modified polysiloxane is obtained by reacting tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium, and dimethyl-3-chloropropylchlorosilane.

[0008] As an optimization, the modified titanium dioxide nanosheets are obtained by reacting titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane with ester phthalocyanine and then hydrolyzing them.

[0009] A method for preparing an anti-aging and anti-corrosion coating, the preparation method comprising the following steps:

[0010] (1) Weigh n-butyl lithium hexane solution, tetrahydrofuran solution, cyclosiloxane solution, and dimethyl-3-chloropropylchlorosilane in a mass ratio of 1:(1-1.2):(4-4.5):(0.4-0.6), and add the n-butyl lithium hexane solution dropwise to the tetrahydrofuran solution at a rate of 0.2 mL / min. After the addition is completed, keep the mixture for 30 min, continue to add the cyclosiloxane solution dropwise at a rate of 1 mL / min. After the addition is completed, keep the mixture at -10 °C for 30 min. n, after the reaction is completed, the temperature is raised to 30°C, and the reaction is continued for 12 hours. After the reaction is completed, dimethyl-3-chloropropylchlorosilane is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the reaction is continued for 60 minutes, the temperature is raised to 80°C, and the reaction is carried out at 80°C for 40-50 minutes. Then, the filtrate is filtered and retained, and distilled at 160°C and 0.2 kPa for 40-50 minutes. The temperature is lowered to room temperature, activated carbon is used for decolorization, and the mixture is filtered and washed with methanol for 3 times, and dried at room temperature for 12 hours to obtain modified polysiloxane;

[0011] (2) 4-vinylpyridine, methyl methacrylate, n-butyl acrylate, and toluene are mixed in a mass ratio of 1:4:5.5:(20-30), heated to 80-90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuo at 80° C. for 24 hours to obtain a pyridyl acrylic resin;

[0012] (3) mixing pyridyl acrylic resin, triethylamine, modified polysiloxane and dichloromethane in a mass ratio of 1:(0.3-0.5):(0.8-0.9):(20-30), heating to 70-80° C., reacting for 12 h, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, drying the organic layer in air at 45° C. for 12 h, and then vacuum drying at 50° C. for 20 h to obtain a polysiloxane-modified acrylic resin;

[0013] (4) mixing polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide in a mass ratio of 1:(2-3):(0.5-0.7):(20-30), reacting at room temperature for 24 hours, adding pure water 3-4 times the volume of dimethyl sulfoxide, filtering, and drying at room temperature for 24 hours to obtain a pre-modified acrylic resin;

[0014] (5) Pre-modified acrylic resin, p-aminodiphenylamine, potassium tert-butoxide, and dioxane are mixed in a mass ratio of 1:(3-4):(3-4):(50-60), heated to 90° C. for reaction for 4-5 hours, and after the reaction, pure water 3-4 times the volume of dioxane is added, filtered, washed with pure water 3-4 times, and dried at room temperature for 24 hours to obtain a modified acrylic resin;

[0015] (6) Pretreated titanium dioxide nanosheets, ester phthalocyanine, anhydrous zinc acetate, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2-3):0.05:(20-30), heated to 70-80°C for reaction for 60 min under nitrogen protection and a pressure of 1.0 MPa, filtered and washed with pure water 3-4 times, redispersed in a 10% sodium hydroxide solution with a mass fraction of 50-60 times the mass of the pretreated titanium dioxide nanosheets, heated to 100°C for reaction for 3-4 h, filtered and washed with pure water 3-4 times, and dried at 50-60°C for 7-8 h to obtain modified titanium dioxide nanosheets;

[0016] (7) The modified acrylic resin, the modified titanium dioxide nanosheets, the solvent, the dispersant and the defoaming agent are mixed in a high-speed disperser to obtain an anti-aging and anti-corrosion coating.

[0017] As an optimization, the n-butyl lithium hexane solution in step (1) is prepared by mixing n-butyl lithium and hexane, and the concentration of n-butyl lithium is 2.4 mol / L; the water content of the tetrahydrofuran solution is 150 ppm; and the cyclosiloxane solution is prepared by uniformly mixing tetramethyltetravinylcyclotetrasiloxane and tetrahydrofuran in a mass ratio of 1:2.

[0018] As an optimization, the initiator solution in step (2) is obtained by mixing ammonium persulfate and pure water in a mass ratio of 1:20.

[0019] As an optimization, the preparation method of the bis(4-chlorophenyl)phosphine in step (4) is as follows: under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane are mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass that is 5 times that of bis(4-chlorophenyl)phosphine oxide; under sealed conditions, the temperature is raised to 60° C. and reacted for 20 hours; isopropanol with a volume that is 0.2 times that of acetonitrile is added; and acetonitrile is removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine.

[0020] As an optimization, the preparation method of the pretreated titanium dioxide nanosheets in step (6) is: titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:30, reacted at 85°C and pH 6 for 6 hours, allowed to stand at room temperature for 18 hours, filtered and washed 4 times with isopropanol to obtain pretreated titanium dioxide nanosheets.

[0021] As an optimization, the preparation method of the ester phthalocyanine in step (6) is as follows: 4,5-dichlorophthalonitrile, 5-hydroxyisophthalic acid dimethyl ester, potassium carbonate, and N,N-dimethylformamide are mixed in a mass ratio of 1:4.28:16.6:60, reacted at 65°C for 24 hours, added with an ice-water mixture 4 times the mass of N,N-dimethylformamide, extracted with chloroform, dehydrated with magnesium sulfate, filtered, recrystallized with methanol, and dried at room temperature for 2 hours. 4h to obtain 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile; under nitrogen protection, 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile, anhydrous cupric chloride, n-pentanol and 1,8-diazabicyclo[5.4.0]undec-7-ene were mixed, heated to 120°C for 3h, cooled to 95°C, n-pentanol was removed under reduced pressure, filtered and washed 3 times with methanol, and dried at room temperature for 24h to obtain ester phthalocyanine.

[0022] As an optimization, the mass ratio of the modified acrylic resin, modified titanium dioxide nanosheets, solvent, dispersant and defoaming agent in step (7) is 1:(0.2-0.3):(20-30):(0.01-0.03):(0.01-0.03), the solvent is propylene glycol ether acetate; the defoaming agent model is AGITAN208; and the dispersant model is OP-10.

[0023] As an optimization, the preparation method of the titanium dioxide nanosheets is: adding hydrofluoric acid to butyl titanate and stirring for 20-30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 3-5 times, and drying at 60°C for 10-12 hours to obtain titanium dioxide nanosheets.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] When preparing the anti-aging and anti-corrosion coating, the present invention firstly reacts tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropyl chlorosilane to obtain modified polysiloxane, then copolymerizes 4-vinylpyridine, methyl methacrylate and n-butyl acrylate to obtain pyridyl acrylic resin, reacts the pyridyl acrylic resin with the modified polysiloxane, then grafts bis(4-chlorophenyl)phosphine, and finally reacts with p-aminodiphenylamine to obtain modified acrylic resin; secondly, reacts titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane with ester-based phthalocyanine, and then hydrolyzes to obtain modified titanium dioxide nanosheets; finally, mixes the modified acrylic resin, the modified titanium dioxide nanosheets, a solvent, a dispersant and a defoaming agent to obtain the anti-aging and anti-corrosion coating.

[0026] First, tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropyl chlorosilane are reacted to obtain modified polysiloxane. Tetramethyltetravinylcyclotetrasiloxane is ring-opened under the action of n-butyl lithium and reacts with dimethyl-3-chloropropyl chlorosilane to obtain polysiloxane with a chloropropyl end group and a double bond in the side chain. The polysiloxane has excellent thermal stability and hydrophobicity and can well block the erosion of external moisture. 4-vinylpyridine, methyl methacrylate and n-butyl acrylate are copolymerized to obtain pyridyl acrylic resin. The pyridyl acrylic resin It reacts with a modified polysiloxane having a chloropropyl terminal group to generate a quaternary ammonium salt structure with antibacterial properties, thereby giving the coating certain antibacterial properties. Then, phosphorus hydrogen on bis(4-chlorophenyl)phosphine and the double bond of the polysiloxane side chain undergo addition, and the phosphorus element with flame retardant function grafted thereon can cooperate with the polysiloxane for flame retardancy, thereby further improving the flame retardant properties of the coating. Finally, the chlorobenzene on bis(4-chlorophenyl)phosphine reacts with p-aminodiphenylamine to generate a p-phenylenediamine structure, which can well prevent ozone, thermal oxygen and fatigue aging, thereby giving the coating good anti-aging properties.

[0027] Secondly, the titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane are reacted with ester phthalocyanine, and then hydrolyzed to obtain modified titanium dioxide nanosheets; the sheet structure of the titanium dioxide nanosheets can form a barrier layer well to prevent the corrosion of the substrate by moisture and oxygen in the air, and the amino groups on the surface of the titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane can react with the methyl ester on the ester phthalocyanine to fix the ester phthalocyanine on the surface of the titanium dioxide nanosheets, and the large conjugated planar structure of phthalocyanine can effectively absorb ultraviolet rays, giving the coating good resistance to ultraviolet aging, and the excess ester groups on the phthalocyanine can be hydrolyzed to become carboxylic acids;

[0028] Finally, the modified acrylic resin, modified titanium dioxide nanosheets, solvent, dispersant and defoaming agent are mixed to obtain an anti-aging and anti-corrosion coating. The carboxylic acid obtained by hydrolysis of the ester group on the surface of the modified titanium dioxide can attract the positive and negative charges of the acrylic resin containing a positively charged quaternary ammonium salt structure, thereby making the titanium dioxide nanosheets evenly dispersed in the coating to avoid agglomeration. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The n-butyl lithium hexane solution used in the following examples and comparative examples is prepared by mixing n-butyl lithium and hexane, and the n-butyl lithium concentration is 2.4 mol / L; the water content of the tetrahydrofuran solution used is 150 ppm; the cyclosiloxane solution used is obtained by uniformly mixing tetramethyltetravinylcyclotetrasiloxane and tetrahydrofuran in a mass ratio of 1:2; the initiator solution used is obtained by mixing ammonium persulfate and pure water in a mass ratio of 1:20; the solvent used is propylene glycol ether acetate; the defoamer model used is AGITAN208; and the dispersant model used is OP-10.

[0031] Embodiment 1:

[0032] A method for preparing an anti-aging and anti-corrosion coating, the preparation method comprising the following steps:

[0033] (1) Weigh n-butyl lithium hexane solution, tetrahydrofuran solution, cyclosiloxane solution, and dimethyl-3-chloropropylchlorosilane in a mass ratio of 1:1:4:0.4, and add n-butyl lithium hexane solution dropwise to the tetrahydrofuran solution at a rate of 0.2 mL / min. After the addition is completed, keep the temperature for 30 minutes, continue to add the cyclosiloxane solution dropwise at a rate of 1 mL / min. After the addition is completed, keep the temperature at -10°C for 30 minutes, and then end the reaction. After that, the temperature was raised to 30°C, and the reaction was continued for 12 hours. After the reaction was completed, dimethyl-3-chloropropylchlorosilane was added dropwise at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 60 minutes, the temperature was raised to 80°C, and the reaction was carried out at 80°C for 50 minutes. The filtrate was then filtered and retained, and distilled at 160°C and 0.2 kPa for 50 minutes. The mixture was cooled to room temperature, decolorized with activated carbon, filtered, and washed with methanol for 3 times, and dried at room temperature for 12 hours to obtain modified polysiloxane.

[0034] (2) 4-vinylpyridine, methyl methacrylate, n-butyl acrylate, and toluene were mixed in a mass ratio of 1:4:5.5:20, heated to 90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 min, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 min, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 min, and finally dried in vacuo at 80° C. for 24 h to obtain a pyridyl acrylic resin;

[0035] (3) Pyridine acrylic resin, triethylamine, modified polysiloxane, and dichloromethane were mixed in a mass ratio of 1:0.3:0.8:20, heated to 80°C, reacted for 12 hours, added with a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, and the organic layer was dried in air at 45°C for 12 hours, and then vacuum dried at 50°C for 20 hours to obtain a polysiloxane-modified acrylic resin;

[0036] (4) Under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane were mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass of 5 times that of bis(4-chlorophenyl)phosphine oxide, and the mixture was heated to 60°C for reaction for 20 hours under sealed conditions, and isopropanol with a volume of 0.2 times that of acetonitrile was added, and the acetonitrile was removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine; polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide were mixed in a mass ratio of 1:2:0.5:20, and the mixture was reacted at room temperature for 24 hours, and pure water with a volume of 4 times that of dimethyl sulfoxide was added, filtered, and dried at room temperature for 24 hours to obtain a pre-modified acrylic resin;

[0037] (5) Pre-modified acrylic resin, p-aminodiphenylamine, potassium tert-butoxide, and dioxane were mixed in a mass ratio of 1:3:3:50, heated to 90° C. for reaction for 5 h, and after the reaction, pure water 3 times the volume of dioxane was added, filtered, washed with pure water 3 times, and dried at room temperature for 24 h to obtain a modified acrylic resin;

[0038] (6) adding hydrofluoric acid to butyl titanate and stirring for 30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 5 times, and drying at 60°C for 12 hours to obtain titanium dioxide nanosheets; mixing titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.5:30, reacting at 85°C and pH 6, The reaction mixture was stirred for 6 hours, allowed to stand at room temperature for 18 hours, filtered and washed 4 times with isopropanol to obtain pretreated titanium dioxide nanosheets; 4,5-dichlorophthalonitrile, 5-hydroxyisophthalic acid dimethyl ester, potassium carbonate and N,N-dimethylformamide were mixed in a mass ratio of 1:4.28:16.6:60, reacted at 65°C for 24 hours, an ice-water mixture 4 times the mass of N,N-dimethylformamide was added, extracted with chloroform, dehydrated with magnesium sulfate, filtered and recrystallized with methanol, and dried at room temperature. 24h, to obtain 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile; under nitrogen protection, 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile, anhydrous cupric chloride, n-pentanol, 1,8-diazabicyclo[5.4.0]undec-7-ene were mixed, heated to 120°C for 3h, cooled to 95°C, n-pentanol was removed under reduced pressure, filtered and washed with methanol for 3 times, and dried at room temperature for 24h to obtain ester phthalocyanine; pretreated titanium dioxide nanosheets, ester Phthalocyanine, anhydrous zinc acetate, and N,N-dimethylformamide were mixed in a mass ratio of 1:2:0.05:20, heated to 80°C for reaction for 60 minutes under nitrogen protection and a pressure of 1.0 MPa, filtered and washed with pure water 4 times, redispersed in a 10% sodium hydroxide solution with a mass fraction of 50 times the mass of the pretreated titanium dioxide nanosheets, heated to 100°C for reaction for 4 hours, filtered and washed with pure water 4 times, and dried at 60°C for 8 hours to obtain modified titanium dioxide nanosheets;

[0039] (7) The modified acrylic resin, the modified titanium dioxide nanosheets, the solvent, the dispersant, and the defoaming agent are mixed in a high-speed disperser at a mass ratio of 1:0.2:20:0.01:0.01 to obtain an anti-aging and anti-corrosion coating.

[0040] Embodiment 2:

[0041] A method for preparing an anti-aging and anti-corrosion coating, the preparation method comprising the following steps:

[0042] (1) Weigh n-butyl lithium hexane solution, tetrahydrofuran solution, cyclosiloxane solution, and dimethyl-3-chloropropylchlorosilane in a mass ratio of 1:1.1:4.3:0.5, and add the n-butyl lithium hexane solution dropwise to the tetrahydrofuran solution at a dropping speed of 0.2 mL / min. After the addition is completed, keep the temperature for 30 minutes, continue to drop the cyclosiloxane solution at a dropping speed of 1 mL / min. After the addition is completed, keep the temperature at -10°C for 30 minutes. After the reaction, the temperature was raised to 30°C, and the reaction was continued for 12 hours. After the reaction was completed, dimethyl-3-chloropropylchlorosilane was added dropwise at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 60 minutes, the temperature was raised to 80°C, and the reaction was carried out at 80°C for 45 minutes. The filtrate was then filtered and retained, and distilled at 160°C and 0.2 kPa for 45 minutes. The filtrate was cooled to room temperature, decolorized with activated carbon, filtered, and washed with methanol for 3 times, and dried at room temperature for 12 hours to obtain modified polysiloxane.

[0043] (2) 4-vinylpyridine, methyl methacrylate, n-butyl acrylate, and toluene were mixed in a mass ratio of 1:4:5.5:25, heated to 85° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuo at 80° C. for 24 hours to obtain a pyridine-based acrylic resin;

[0044] (3) Pyridine acrylic resin, triethylamine, modified polysiloxane, and dichloromethane were mixed in a mass ratio of 1:0.4:0.85:25, heated to 75°C, reacted for 12 hours, added with a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, and the organic layer was dried in air at 45°C for 12 hours, and then vacuum dried at 50°C for 20 hours to obtain a polysiloxane-modified acrylic resin;

[0045] (4) Under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane were mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass of 5 times that of bis(4-chlorophenyl)phosphine oxide, and the mixture was heated to 60°C for reaction for 20 hours under sealed conditions, and isopropanol with a volume of 0.2 times that of acetonitrile was added, and the acetonitrile was removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine; polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide were mixed in a mass ratio of 1:2.5:0.6:25, and the mixture was reacted at room temperature for 24 hours, and pure water with a volume of 3 times that of dimethyl sulfoxide was added, filtered, and dried at room temperature for 24 hours to obtain a pre-modified acrylic resin;

[0046] (5) Pre-modified acrylic resin, p-aminodiphenylamine, potassium tert-butoxide, and dioxane were mixed in a mass ratio of 1:3.5:3.5:55, heated to 90° C. and reacted for 4.5 hours. After the reaction, 3.5 times the volume of dioxane was added with pure water, filtered, washed with pure water for 3 times, and dried at room temperature for 24 hours to obtain a modified acrylic resin;

[0047] (6) adding hydrofluoric acid to butyl titanate and stirring for 25 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 4 times, and drying at 60°C for 11 hours to obtain titanium dioxide nanosheets; mixing titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.5:30, reacting at 85°C and pH 6 6h, let stand at room temperature for 18h, filter and wash 4 times with isopropanol to obtain pretreated titanium dioxide nanosheets; 4,5-dichlorophthalonitrile, 5-hydroxyisophthalic acid dimethyl ester, potassium carbonate, and N,N-dimethylformamide are mixed in a mass ratio of 1:4.28:16.6:60, reacted at 65°C for 24h, added with an ice-water mixture 4 times the mass of N,N-dimethylformamide, extracted with chloroform, dehydrated with magnesium sulfate, filtered, recrystallized with methanol, and dried at room temperature for 24h , to obtain 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile; under nitrogen protection, 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile, anhydrous cupric chloride, n-pentanol, and 1,8-diazabicyclo[5.4.0]undec-7-ene were mixed, heated to 120°C for reaction for 3h, cooled to 95°C, n-pentanol was removed under reduced pressure, filtered and washed with methanol for 3 times, and dried at room temperature for 24h to obtain ester phthalocyanine; pretreated titanium dioxide nanosheets, ester phthalocyanine, and anhydrous cupric chloride were added to obtain phthalocyanine. Aqueous zinc acetate and N,N-dimethylformamide were mixed in a mass ratio of 1:2.5:0.05:25, heated to 75°C for reaction for 60 minutes under nitrogen protection and a pressure of 1.0 MPa, filtered and washed with pure water three times, redispersed in a 10% sodium hydroxide solution with a mass fraction of 55 times the mass of the pretreated titanium dioxide nanosheets, heated to 100°C for reaction for 3.5 hours, filtered and washed with pure water three times, and dried at 55°C for 7.5 hours to obtain modified titanium dioxide nanosheets;

[0048] (7) The modified acrylic resin, the modified titanium dioxide nanosheets, the solvent, the dispersant, and the defoaming agent are mixed in a high-speed disperser at a mass ratio of 1:0.25:25:0.02:0.02 to obtain an anti-aging and anti-corrosion coating.

[0049] Embodiment 3:

[0050] A method for preparing an anti-aging and anti-corrosion coating, the method comprising the following steps:

[0051] (1) n-Butyl lithium hexane solution, tetrahydrofuran solution, cyclosiloxane solution, and dimethyl-3-chloropropylchlorosilane were weighed in a mass ratio of 1:1.2:4.5:0.6. The n-Butyl lithium hexane solution was added dropwise to the tetrahydrofuran solution at a rate of 0.2 mL / min. After the addition was completed, the reaction was maintained for 30 min. The cyclosiloxane solution was continued to be added dropwise at a rate of 1 mL / min. After the addition was completed, the reaction was continued at -10 °C for 30 min. After the reaction, the temperature was raised to 30°C, and the reaction was continued for 12 hours. After the reaction was completed, dimethyl-3-chloropropylchlorosilane was added dropwise at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 60 minutes, the temperature was raised to 80°C, and the reaction was carried out at 80°C for 40 minutes. The filtrate was then filtered and retained, and distilled at 160°C and 0.2 kPa for 40 minutes. The filtrate was cooled to room temperature, decolorized with activated carbon, filtered, and washed with methanol for 3 times, and dried at room temperature for 12 hours to obtain modified polysiloxane.

[0052] (2) 4-vinylpyridine, methyl methacrylate, n-butyl acrylate, and toluene are mixed in a mass ratio of 1:4:5.5:30, heated to 80° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuo at 80° C. for 24 hours to obtain a pyridine-based acrylic resin;

[0053] (3) Pyridine acrylic resin, triethylamine, modified polysiloxane, and dichloromethane were mixed in a mass ratio of 1:0.5:0.9:30, heated to 70°C, reacted for 12 hours, added with a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, and the organic layer was dried in air at 45°C for 12 hours, and then vacuum dried at 50°C for 20 hours to obtain a polysiloxane-modified acrylic resin;

[0054] (4) Under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane were mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass of 5 times that of bis(4-chlorophenyl)phosphine oxide, and the mixture was heated to 60°C for reaction for 20 hours under sealed conditions, and isopropanol with a volume of 0.2 times that of acetonitrile was added, and the acetonitrile was removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine; polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide were mixed in a mass ratio of 1:3:0.7:30, and the mixture was reacted at room temperature for 24 hours, and pure water with a volume of 4 times that of dimethyl sulfoxide was added, filtered, and dried at room temperature for 24 hours to obtain a pre-modified acrylic resin;

[0055] (5) Pre-modified acrylic resin, p-aminodiphenylamine, potassium tert-butoxide, and dioxane were mixed in a mass ratio of 1:4:4:60, heated to 90° C. for reaction for 4 h, and after the reaction, pure water 3 times the volume of dioxane was added, filtered, washed with pure water 3 times, and dried at room temperature for 24 h to obtain a modified acrylic resin;

[0056] (6) adding hydrofluoric acid to butyl titanate and stirring for 20 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400 r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 3 times, and drying at 60°C for 10 hours to obtain titanium dioxide nanosheets; mixing titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.5:30, and reacting at 85°C and pH 6. The reaction mixture was stirred for 6 hours, allowed to stand at room temperature for 18 hours, filtered and washed 4 times with isopropanol to obtain pretreated titanium dioxide nanosheets; 4,5-dichlorophthalonitrile, 5-hydroxyisophthalic acid dimethyl ester, potassium carbonate and N,N-dimethylformamide were mixed in a mass ratio of 1:4.28:16.6:60, reacted at 65°C for 24 hours, an ice-water mixture 4 times the mass of N,N-dimethylformamide was added, extracted with chloroform, dehydrated with magnesium sulfate, filtered and recrystallized with methanol, and dried at room temperature. 24h, to obtain 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile; under nitrogen protection, 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile, anhydrous cupric chloride, n-pentanol, 1,8-diazabicyclo[5.4.0]undec-7-ene were mixed, heated to 120°C for 3h, cooled to 95°C, n-pentanol was removed under reduced pressure, filtered and washed with methanol for 3 times, and dried at room temperature for 24h to obtain ester phthalocyanine; pretreated titanium dioxide nanosheets, ester Phthalocyanine, anhydrous zinc acetate, and N,N-dimethylformamide were mixed in a mass ratio of 1:3:0.05:30, heated to 70°C for reaction for 60 minutes under nitrogen protection and a pressure of 1.0 MPa, filtered and washed with pure water three times, redispersed in a 10% sodium hydroxide solution with a mass fraction of 60 times the mass of the pretreated titanium dioxide nanosheets, heated to 100°C for reaction for 3 hours, filtered and washed with pure water three times, and dried at 50°C for 7 hours to obtain modified titanium dioxide nanosheets;

[0057] (7) The modified acrylic resin, the modified titanium dioxide nanosheets, the solvent, the dispersant, and the defoaming agent are mixed in a high-speed disperser at a mass ratio of 1:0.3:30:0.03:0.03 to obtain an anti-aging and anti-corrosion coating.

[0058] Comparative Example 1:

[0059] The preparation method of the anti-aging and anti-corrosion coating of Comparative Example 1 differs from that of Example 2 in that the method does not contain steps (1), (3), (4) and (5), and step (2) is modified as follows: 4-vinylpyridine, methyl methacrylate, n-butyl acrylate and toluene are mixed in a mass ratio of 1:4:5.5:25, heated to 85°C under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, finally dried in vacuo at 80°C for 24 hours to obtain a modified acrylic resin.

[0060] Comparative Example 2:

[0061] The preparation method of the anti-aging and anti-corrosion coating of Comparative Example 2 differs from that of Example 2 in that steps (4) and (5) are not included, and step (3) is modified as follows: pyridyl acrylic resin, triethylamine, modified polysiloxane and dichloromethane are mixed in a mass ratio of 1:0.4:0.85:25, the mixture is heated to 75° C., reacted for 12 h, an equal volume of saturated sodium bicarbonate aqueous solution to that of dichloromethane is added, the organic layer is dried in air at 45° C. for 12 h, and then vacuum dried at 50° C. for 20 h to obtain a modified acrylic resin.

[0062] Comparative Example 3:

[0063] The preparation method of the anti-aging and anti-corrosion coating of Comparative Example 3 differs from that of Example 2 in that step (5) is not included, and step (4) is modified as follows: under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane are mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass of 5 times that of bis(4-chlorophenyl)phosphine oxide; under sealed conditions, the temperature is raised to 60° C. for reaction for 20 h; isopropanol with a volume of 0.2 times that of acetonitrile is added; acetonitrile is removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine; polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide are mixed in a mass ratio of 1:2.5:0.6:25, reacted at room temperature for 24 h, pure water with a volume of 3 times that of dimethyl sulfoxide is added, filtered, and dried at room temperature for 24 h to obtain a modified acrylic resin.

[0064] Comparative Example 4:

[0065] The difference between the preparation method of the anti-aging and anti-corrosion coating of Comparative Example 4 and Example 2 is that step (6) is modified as follows: adding hydrofluoric acid to butyl titanate and stirring for 25 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water 4 times, and drying at 60°C for 11 hours to obtain titanium dioxide nanosheets; titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:30, reacting at 85°C and pH 6 for 6 hours, standing at room temperature for 18 hours, filtering and washing with isopropanol 4 times to obtain modified titanium dioxide nanosheets.

[0066] Test Example 1:

[0067] Flame retardant performance test:

[0068] Test method: The coating prepared in the comparative example of the embodiment was poured into a polytetrafluoroethylene mold with a size of 125mm*15mm*8mm, placed in an oven at 80°C for drying for 24 hours to make a specimen. After taking out the dried specimen, it was tested with a JF-3 limiting oxygen index instrument. The results are shown in Table 1.

[0069] Table 1

[0070] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.5 Comparative Example 1 22.3 Example 2 31.7 Comparative Example 2 25.4 Example 3 31.5 Comparative Example 3 31.4 Comparative Example 4 29.7

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good flame retardancy.

[0072] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 1 and 2, indicating that first, tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropyl chlorosilane are reacted to obtain modified polysiloxane, and tetramethyltetravinylcyclotetrasiloxane is ring-opened under the action of n-butyl lithium, and reacts with dimethyl-3-chloropropyl chlorosilane to obtain a polysiloxane with a chloropropyl end group and a double bond in the side chain. The polysiloxane has excellent thermal stability and hydrophobicity, and can well block the erosion of external moisture; 4-vinylpyridine, methyl methacrylate, and n-butyl acrylate are copolymerized to obtain a pyridyl acrylic resin, and then the phosphorus hydrogen on the bis(4-chlorophenyl)phosphine and the double bond of the polysiloxane side chain are added, and the phosphorus element with flame retardant function is grafted, which can cooperate with the polysiloxane to flame retard, and further improve the flame retardant performance of the coating.

[0073] Test Example 2:

[0074] Antibacterial performance test:

[0075] Test method: The antibacterial rate of the coatings prepared in all embodiments and comparative examples was tested according to the standard GB / T 21866--2008. The results are shown in Table 2.

[0076] Table 2

[0077] Antibacterial rate (%) Antibacterial rate (%) Example 1 97.21 Comparative Example 1 23.46 Example 2 96.89 Comparative Example 2 96.57 Example 3 97.36 Comparative Example 3 96.76 Comparative Example 4 90.43

[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good antibacterial properties.

[0079] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropylchlorosilane are reacted to obtain modified polysiloxane, tetramethyltetravinylcyclotetrasiloxane is ring-opened under the action of n-butyl lithium, and reacts with dimethyl-3-chloropropylchlorosilane to obtain a polysiloxane having a chloropropyl end group and a double bond in the side chain, 4-vinylpyridine, methyl methacrylate and n-butyl acrylate are copolymerized to obtain a pyridyl acrylic resin, and the pyridyl acrylic resin reacts with the modified polysiloxane having a chloropropyl end group to generate a quaternary ammonium salt structure with antibacterial properties, thereby giving the coating certain antibacterial properties.

[0080] Test Example 3:

[0081] Tests for anti-corrosion and anti-aging properties:

[0082] Salt water resistance test: According to the standard GB 1763 / 1979, after grinding, cleaning and drying the surface of a steel plate with a size of 120mm*50mm*0.5mm, the coating was applied to the surface of the steel plate to make a sample, and the coating thickness was 100μm. After drying at room temperature for 7 days, the sample was placed in a 5wt% sodium chloride solution at 25℃, and 2 / 3 of the length of each sample was immersed in the sodium chloride solution for 600h, and the appearance of the sample was observed; before the sample was immersed in the sodium chloride solution, a paraffin and rosin mixture was used to seal the edge, and the edge width was 2.3mm. The paraffin rosin mixture was made by mixing paraffin and rosin at a mass ratio of 1:1. The results are shown in Table 3.

[0083] UV aging resistance test: According to GB 1763 / 1979, after grinding, cleaning and drying the surface of a steel plate with a size of 120mm*50mm*0.5mm, the coating was applied on the surface of the steel plate to make a sample, and the coating thickness was 100μm. After drying at room temperature for 7 days, it was placed in a UV aging box for irradiation. The temperature in the aging box was 50℃, the irradiation time was 720h, the wavelength of the UV light was 340nm, the light power was 40W, and the distance between the coating and the light source was 50mm. The appearance of the sample was observed. The results are shown in Table 3.

[0084] Thermal oxygen aging resistance test: According to the standard GB 1763 / 1979, after grinding, cleaning and drying the surface of a steel plate with a size of 120mm*50mm*0.5mm, the coating was applied on the surface of the steel plate to make a sample, and the coating thickness was 100μm. After drying at room temperature for 7 days, it was placed in a 401AB type heating blast drying oven, the test temperature was 60℃, the test time was 720h, and the appearance of the sample was observed. The results are shown in Table 3.

[0085] Table 3

[0086]

[0087] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good corrosion resistance and anti-aging properties.

[0088] By comparison, the appearance of Examples 1 to 3 after the salt water resistance test is better than that of Comparative Example 1, the appearance of Examples 1 to 3 after the UV aging resistance test is better than that of Comparative Example 4, and the appearance of Examples 1 to 3 after the heat oxygen aging resistance test is better than that of Comparative Examples 1 to 3, indicating that first, tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropylchlorosilane are reacted to obtain modified polysiloxane, tetramethyltetravinylcyclotetrasiloxane is ring-opened under the action of n-butyl lithium, and reacts with dimethyl-3-chloropropylchlorosilane to obtain a polysiloxane with a single terminal group of chloropropyl and a double bond in the side chain, and the polysiloxane Oxane has excellent thermal stability and hydrophobicity, and can well block the erosion of external moisture; 4-vinylpyridine, methyl methacrylate, and n-butyl acrylate are copolymerized to obtain pyridyl acrylic resin, and the pyridyl acrylic resin is reacted with a modified polysiloxane having a chloropropyl end group, and then addition occurs through the phosphorus hydrogen on the bis(4-chlorophenyl)phosphine and the double bond of the polysiloxane side chain, and finally the chlorobenzene on the bis(4-chlorophenyl)phosphine reacts with p-aminodiphenylamine to generate a p-phenylenediamine structure, which can well prevent ozone, thermal oxygen, and fatigue aging, thereby giving the coating good anti-aging properties;

[0089] Secondly, the titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane are reacted with ester phthalocyanine and then hydrolyzed to obtain modified titanium dioxide nanosheets; the amino groups on the surface of the titanium dioxide nanosheets pretreated with 3-aminopropyltrimethoxysilane can react with the methyl ester on the ester phthalocyanine to fix the ester phthalocyanine on the surface of the titanium dioxide nanosheets, and the large conjugated planar structure of phthalocyanine can effectively absorb ultraviolet rays.

[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An anti-aging and anti-corrosion coating, characterized in that: The anti-aging and anti-corrosion coating is obtained by mixing modified acrylic resin, modified titanium dioxide nanosheets, solvent, dispersant and defoamer; The modified acrylic resin is obtained by copolymerizing 4-vinylpyridine, methyl methacrylate and n-butyl acrylate to obtain a pyridyl acrylic resin; the pyridyl acrylic resin is reacted with a modified polysiloxane, then grafted with bis(4-chlorophenyl)phosphine, and finally reacted with p-aminodiphenylamine; the modified polysiloxane is obtained by reacting tetramethyltetravinylcyclotetrasiloxane, n-butyl lithium and dimethyl-3-chloropropylchlorosilane; The modified titanium dioxide nanosheet is obtained by reacting the titanium dioxide nanosheet pretreated with 3-aminopropyltrimethoxysilane with ester phthalocyanine and then hydrolyzing it.

2. A method for preparing an anti-aging and anti-corrosion coating, characterized in that: The preparation method comprises the following steps: (1) Weigh n-butyl lithium hexane solution, tetrahydrofuran solution, cyclosiloxane solution, and dimethyl-3-chloropropylchlorosilane in a mass ratio of 1:(1-1.2):(4-4.5):(0.4-0.6), and add the n-butyl lithium hexane solution dropwise to the tetrahydrofuran solution at a rate of 0.2 mL / min. After the addition is completed, keep the mixture for 30 min, continue to add the cyclosiloxane solution dropwise at a rate of 1 mL / min. After the addition is completed, keep the mixture at -10 °C for 30 min. n, after the reaction is completed, the temperature is raised to 30°C, and the reaction is continued for 12 hours. After the reaction is completed, dimethyl-3-chloropropylchlorosilane is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the reaction is continued for 60 minutes, the temperature is raised to 80°C, and the reaction is carried out at 80°C for 40-50 minutes. Then, the filtrate is filtered and retained, and distilled at 160°C and 0.2 kPa for 40-50 minutes. The temperature is lowered to room temperature, activated carbon is used for decolorization, and the mixture is filtered and washed with methanol for 3 times, and dried at room temperature for 12 hours to obtain modified polysiloxane; (2) 4-vinylpyridine, methyl methacrylate, n-butyl acrylate, and toluene are mixed in a mass ratio of 1:4:5.5:(20-30), heated to 80-90° C. under nitrogen protection, added with an initiator solution of 0.3 times the volume of toluene, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, then added with an initiator solution of 0.3 times the volume of toluene again, stirred for 90 minutes, and finally dried in vacuo at 80° C. for 24 hours to obtain a pyridyl acrylic resin; (3) mixing pyridyl acrylic resin, triethylamine, modified polysiloxane and dichloromethane in a mass ratio of 1:(0.3-0.5):(0.8-0.9):(20-30), heating to 70-80° C., reacting for 12 h, adding a saturated sodium bicarbonate aqueous solution having an equal volume to that of dichloromethane, drying the organic layer in air at 45° C. for 12 h, and then vacuum drying at 50° C. for 20 h to obtain a polysiloxane-modified acrylic resin; (4) mixing polysiloxane-modified acrylic resin, bis(4-chlorophenyl)phosphine, cesium carbonate, and dimethyl sulfoxide in a mass ratio of 1:(2-3):(0.5-0.7):(20-30), reacting at room temperature for 24 hours, adding pure water 3-4 times the volume of dimethyl sulfoxide, filtering, and drying at room temperature for 24 hours to obtain a pre-modified acrylic resin; (5) Pre-modified acrylic resin, p-aminodiphenylamine, potassium tert-butoxide, and dioxane are mixed in a mass ratio of 1:(3-4):(3-4):(50-60), heated to 90° C. for reaction for 4-5 hours, and after the reaction, pure water 3-4 times the volume of dioxane is added, filtered, washed with pure water 3-4 times, and dried at room temperature for 24 hours to obtain a modified acrylic resin; (6) Pretreated titanium dioxide nanosheets, ester phthalocyanine, anhydrous zinc acetate, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2-3):0.05:(20-30), heated to 70-80°C for reaction for 60 min under nitrogen protection and a pressure of 1.0 MPa, filtered and washed with pure water 3-4 times, redispersed in a 10% sodium hydroxide solution with a mass fraction of 50-60 times the mass of the pretreated titanium dioxide nanosheets, heated to 100°C for reaction for 3-4 h, filtered and washed with pure water 3-4 times, and dried at 50-60°C for 7-8 h to obtain modified titanium dioxide nanosheets; (7) The modified acrylic resin, the modified titanium dioxide nanosheets, the solvent, the dispersant and the defoaming agent are mixed in a high-speed disperser to obtain an anti-aging and anti-corrosion coating.

3. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The n-butyl lithium hexane solution in step (1) is prepared by mixing n-butyl lithium and hexane, and the concentration of n-butyl lithium is 2.4 mol / L; the water content of the tetrahydrofuran solution is 150 ppm; and the cyclosiloxane solution is prepared by uniformly mixing tetramethyltetravinylcyclotetrasiloxane and tetrahydrofuran in a mass ratio of 1:

2.

4. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The initiator solution in step (2) is obtained by mixing ammonium persulfate and pure water in a mass ratio of 1:

20.

5. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The preparation method of the bis(4-chlorophenyl)phosphine in step (4) is as follows: under an argon atmosphere, bis(4-chlorophenyl)phosphine oxide and pinacol borane are mixed in a molar ratio of 1:1.5 and added to acetonitrile with a mass of 5 times that of bis(4-chlorophenyl)phosphine oxide; under sealed conditions, the temperature is raised to 60° C. and reacted for 20 hours; isopropanol with a volume of 0.2 times that of acetonitrile is added; and acetonitrile is removed by vacuum rotary evaporation to obtain bis(4-chlorophenyl)phosphine.

6. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The preparation method of the pretreated titanium dioxide nanosheets in step (6) is as follows: titanium dioxide nanosheets, 3-aminopropyltrimethoxysilane, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:30, reacted at 85°C and pH 6 for 6 hours, allowed to stand at room temperature for 18 hours, filtered, and washed 4 times with isopropanol to obtain pretreated titanium dioxide nanosheets.

7. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The preparation method of the ester phthalocyanine in step (6) is as follows: 4,5-dichlorophthalonitrile, 5-hydroxyisophthalic acid dimethyl ester, potassium carbonate, and N,N-dimethylformamide are mixed in a mass ratio of 1:4.28:16.6:60, reacted at 65° C. for 24 hours, added with an ice-water mixture of 4 times the mass of N,N-dimethylformamide, extracted with chloroform, dehydrated with magnesium sulfate, filtered, and recrystallized with methanol, and dried at room temperature for 24 hours. 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile is obtained; under nitrogen protection, 4,5-(3,5-dimethoxycarbonyl)phenoxyphthalonitrile, anhydrous cupric chloride, n-pentanol, and 1,8-diazabicyclo[5.4.0]undec-7-ene are mixed, the temperature is raised to 120°C for reaction for 3 hours, the temperature is lowered to 95°C, the n-pentanol is removed under reduced pressure, the mixture is filtered and washed 3 times with methanol, and dried at room temperature for 24 hours to obtain ester phthalocyanine.

8. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: In step (7), the mass ratio of the modified acrylic resin, modified titanium dioxide nanosheets, solvent, dispersant and defoaming agent is 1:(0.2-0.3):(20-30):(0.01-0.03):(0.01-0.03), the solvent is propylene glycol ether acetate; the defoaming agent model is AGITAN208; and the dispersant model is OP-10.

9. The method for preparing an anti-aging and anti-corrosion coating according to claim 6, characterized in that: The preparation method of the titanium dioxide nanosheet is as follows: adding hydrofluoric acid to butyl titanate and stirring for 20-30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 3-5 times, and drying at 60°C for 10-12 hours to obtain the titanium dioxide nanosheet.

Citation Information

Cited By

  • Weather-resistant unsaturated polyester resin as well as preparation method and photovoltaic application thereof

    CN120082184A

  • Preparation method of dipotassium glycyrrhizinate for deeply removing heavy metals based on chelate resin

    CN120795054A